HUBUNGAN FAKTOR INTRINSIK DAN EKSTRINSIK DENGAN RISIKO JATUH LANSIA DI WILAYAH KERJA PUSKESMAS MEDAN SUNGGAL - Rotua Sumihar Sitorus (Jurnal Maternitas Kebidanan, 2020)
Elderly people are prone to risk falling due to morphological changes in muscles, causing muscle functional changes. Elderly residing in the working area of Puskesmas Medan Sunggal at risk of falling can be influenced by intrinsic factors, namely the history of the disease and extrinsic factors such as the condition of the home environment. The purpose of this study was to determine the relationship of intrinsic and extrinsic factors with the risk of falling elderly in the working area of Puskesmas Medan Sunggal. This type of analytic research with cross sectional approach. The population is all elderly aged ≥60 years 143 people and and the sample is 60 people. The sampling technique was purposive sampling. Data were analyzed with the Spearman correlation test. The results showed intrinsic factors so that the elderly avoid the risk of falling are categorized as good (38.5%) and extrinsic factors are sufficient category (53.3%) and low risk of elderly falls (40%). The statistical results show that there is a relationship between intrinsic and extrinsic factors with the risk of falling elderly with a strong enough relationship, that is r = 0.483; r = 0.404 (Strong enough) and p values ​​of 0.000 <0.05 and 0.001 <0.05. It can be concluded that relationship between intrinsic and extrinsic factors with the risk of falling elderly so that nurses provide education to the elderly and family about environmental conditions or a healthy and safe home page, the elderly's daily activities and maintaining and health care related to generative diseases